2016
DOI: 10.1159/000443393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Therapeutic Efficacies of Norethisterone, Tranexamic Acid and Levonorgestrel-Releasing Intrauterine System for the Treatment of Heavy Menstrual Bleeding: A Randomized Controlled Study

Abstract: Background: Our aim was to compare the therapeutic efficacies of norethisterone acid (NETA), tranexamic acid and levonorgestrel-releasing intrauterine system (LNG-IUS) in treating idiopathic heavy menstrual bleeding (HMB). Methods: Women with heavy uterine bleeding were randomized to receive NETA, tranexamic acid or LNG-IUS for 6 months. The primary outcome was a decrease in menstrual bleeding as assessed by pictorial blood loss assessment charts and hematological parameters analyzed at the 1st, 3rd and 6th mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…A total of 13 trials (with 14 references) involving 1,677 women were included [Dong ( 17 ), Endrikat et al ( 18 ), Gupta et al ( 19 , 20 ), Irvine et al ( 21 ), Kaunitz et al ( 22 ), Kavasoglu et al ( 23 ), Kiseli et al ( 24 ), Liu ( 25 ), Malik et al ( 26 ), Reid and Susanna ( 27 ), Shabaan et al ( 28 ), Zhao and Hongyan ( 29 ), and Zhong et al ( 30 )]. Overall, 10 single-center trials were included, of which four were conducted in China ( 17 , 25 , 29 , 30 ) and the remaining six were conducted in Scotland ( 21 ), Turkey ( 24 ), the United Kingdom ( 27 ), Pakistan ( 26 ), and Egypt ( 28 ). The remaining three multicenter trials ( 18 , 20 , 22 ) recruited participants from Canada, the United Kingdom, the United States, and Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 trials (with 14 references) involving 1,677 women were included [Dong ( 17 ), Endrikat et al ( 18 ), Gupta et al ( 19 , 20 ), Irvine et al ( 21 ), Kaunitz et al ( 22 ), Kavasoglu et al ( 23 ), Kiseli et al ( 24 ), Liu ( 25 ), Malik et al ( 26 ), Reid and Susanna ( 27 ), Shabaan et al ( 28 ), Zhao and Hongyan ( 29 ), and Zhong et al ( 30 )]. Overall, 10 single-center trials were included, of which four were conducted in China ( 17 , 25 , 29 , 30 ) and the remaining six were conducted in Scotland ( 21 ), Turkey ( 24 ), the United Kingdom ( 27 ), Pakistan ( 26 ), and Egypt ( 28 ). The remaining three multicenter trials ( 18 , 20 , 22 ) recruited participants from Canada, the United Kingdom, the United States, and Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in concordance with Kiseli et al study, where percentage decrease in PBAC score was reported to be 85.8% in LNG IUS group and 53.1% in norethisterone group. 6 In a study done by Ashraf et al, 94.73% reduction in LNG IUS group was noted as compared to 73% in norethisterone treated group at 6 months. 7 It was observed that both the treatment modalities significantly decreased bleeding duration at completion of study (p=0.000); LNG IUS was more successful than norethisterone in lowering duration of bleeding which was also witnessed in the study done by Lee et al, who compared LNG IUS with conventional medical therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Another randomized controlled study reported that the satisfaction rate was 70% with norethisterone in heavy menstrual bleeding. 23…”
Section: Discussionmentioning
confidence: 99%